Power, interdependence, and nonstate actors in world politics - Milner, Helen V. 1958-; Moravcsik, Andrew (Princeton University Press, 2009)
Since they were pioneered in the 1970s by Robert Keohane and others, the broad range of neoliberal institutionalist theories of international relations have grown in importance. In an increasingly globalized world, the realist and neorealist focus on states, military power, conflict, and anarchy has more and more given way to a recognition of the importance of nonstate actors, nonmilitary forms of power, interdependence, international institutions, and cooperation. Drawing together a group of leading international relations theorists, this book explores the frontiers of new research on the role of such forces in world politics. The topics explored in these chapters include the uneven role of peacekeepers in civil wars, the success of human rights treaties in promoting women's rights, the disproportionate power of developing countries in international environmental policy negotiations, and the prospects for Asian regional cooperation. While all of the chapters demonstrate the empirical and theoretical vitality of liberal and institutionalist theories, they also highlight weaknesses that should drive future research and influence the reform of foreign policy and international organizations.